Chemical variability in volatile composition between several Italian accessions of Siler montanum (S. montanum subsp. montanum and S. montanum subsp. siculum). (February 2017) - Maggi, Filippo; Bartolucci, Fabrizio; Conti, Fabio
Abstract: Laserpitium siler, currently recognized as Siler montanum, is a polymorphic species belonging to the Apiaceae family and distributed in mountains of Southern Europe. In the present work we have analysed five accessions from Italy (Piemonte, Valle d'Aosta and Abruzzo) belonging to S. montanum subsp. montanum and subsp. siculum for the essential oil composition with the aim to find correlations between chemical data and taxonomic relationships. Results, obtained by gas chromatography-mass spectrometry (GC-MS), showed a significant variability, with the subsp. siculum characterized by one chemotype (sabinene/perilla aldehyde/chamazulene), and the subsp. montanum belonging to three different chemotypes (I ( E )-anethole, II sabinene, III limonene). Principal component analysis (PCA) was used to identify the chemical differences among the five accessions according to geographical origin and subspecies. Graphical abstract: Highlights: Laserpitium siler is currently recognized as Siler montanum . Five Italian accessions of S. montanum were investigated for essential oil composition. The subsp. siculum was characterized by sabinene/perilla aldehyde/chamazulene chemotype. The subsp. montanum showed more variability (three chemotypes).